Pengelolaan Bioenergi Berbasis Kayu Lokal: Integrasi Kajian Teknis dan Sosial di Wilayah Perbatasan Indonesia–Timor Leste - Kehi, Maria Y. R.; Dethan, Jemmy Jonson Sula; Koehuan, Jonathan E.; Kette, Arlindo U. S. (Sekolah Tinggi Pertanian Kutai Timur, 2025)
The reliance of border communities on firewood as a primary energy source remains high due to limited access to modern energy. This study aims to examine the bioenergy potential of three locally available wood types commonly used by residents of Alas Selatan Village, Kobalima Timur District, Malaka Regency, East Nusa Tenggara: Leucaena leucocephala (Lamtoro), Tectona grandis (Teak), and Tamarindus indica (Tamarind). A descriptive quantitative and qualitative approach was employed. Laboratory tests were conducted to measure moisture content and ash content as indicators of combustion efficiency. Observations and interviews were carried out to explore community practices in the collection and storage of firewood. The results show that all three wood types exhibit low moisture content (<8%), with Tamarind having the lowest at 7.57%. In terms of ash content, Lamtoro proved to be the most efficient, producing only 1.3% ash, followed by Teak (2.355%) and Tamarind (4.725%). The community applies adaptive firewood storage methods, such as storing wood under stilt houses and above kitchen hearths (para-para), which facilitate effective drying. These findings indicate that the management of locally sourced wood-based bioenergy holds significant potential as a sustainable energy alternative in border regions, particularly when supported by technical education and appropriate conservation policies.